Anxiety Is Associated With Diverse Physical and Cognitive Symptoms in Youth Presenting to a Multidisciplinary Concussion Clinic - Iverson, Grant L.; Greenberg, Jonathan; Cook, Nathan E. (Frontiers in Neurology, 2022)
Introduction Pre-injury and post-injury anxiety are prevalent and important to consider in the medical management of concussions in youth. We examined the association between anxiety and other physical, cognitive, and emotional symptoms in injured adolescents and young adults undergoing an initial evaluation in a specialty concussion clinic. Methods Participants were 158 adolescents and young adults presenting to a multidisciplinary concussion clinic for evaluation and treatment (54.4% girls and women; mean age = 17.3 years; SD = 2.9). Their median days post injury was 29 (interquartile range = 14–49; range = 7–349). They were divided into binary groups based on whether they had a pre-injury history of anxiety diagnosis or treatment and whether they were experiencing current anxiety in the week prior to the evaluation, and then compared on the Post-Concussion Symptom Scale. Results Youth with a pre-injury history of anxiety reported greater post-concussion symptoms (Md total score = 36.0, IQR = 21.5–53.0) compared to youth with no pre-injury history of anxiety (Md total score = 20.5, IQR = 6.0–36.0; MW U = 1,520.00 p = 0.001, r = 0.26, small-medium effect size). They reported significantly worse headaches, nausea, balance difficulty, dizziness, vision problems, fatigue, concentration difficulty, irritability, nervousness, sadness, feeling more emotional, trouble falling asleep, and sleeping more than usual. Youth with high post-injury anxiety reported greater post-concussion symptoms (Md total score = 55.0, IQR = 33.0–62.5) compared to youth with low post-injury anxiety (Md total score = 19.0, IQR = 6.0–35.0; MW U = 681.00, p < 0.001, r = 0.49, large effect size). They reported significantly worse headaches, nausea, vomiting, dizziness, vision problems, fatigue, sensitivity to light, feeling mentally foggy, feeling slowed down, concentration difficulty, memory difficulty, irritability, sadness, feeling more emotional, drowsiness, trouble falling asleep, sleeping less than usual, and sleeping more than usual. Logistic regressions revealed that both pre-injury and post-injury anxiety were strong predictors of persistent post-concussion symptoms, with high post-injury anxiety presenting the strongest independent predictor, while attention-deficit hyperactivity disorder and pre-injury migraines were not significant predictors. Essentially all adolescents with high post-injury anxiety (97.1%) and nearly 9 of 10 adolescents with pre-injury treatment for anxiety (87.8%) met criteria for persistent post-concussion symptoms. Discussion Pre-injury and post-injury anxiety are important risk factors for greater post-concussion symptoms among adolescents and young adults. Elevated post-injury anxiety was the strongest predictor of persistent post-concussion symptoms. Assessment of anxiety is important among adolescents presenting for concussion care and delivery of evidence-supported treatments for anxiety are important considerations for treatment planning for these youth.